Validation of global school-based student health survey in Bahrain - Eman Haji; Ashwaq Sabt; Fatin Hasani; Feddha Abdalrasool; Fatema Jamsheer; Ibtisam Nuhaily; Ghufran Jassim (Cogent Public Health)
The Global school-based student health survey (GSHS) was developed by the World Health Organization (WHO) and Centers for Disease Control (CDC) in affiliation with other organizations to obtain data on young people’s health behaviour and protective factors related to the leading causes of morbidity and mortality among children and young adults. This report discusses results from the first Global school-based student health survey carried out in Bahrain which assesses and measures students’ behavioural risk and protective factors with the aim of promoting health among schoolchildren. The GSHS includes students aged 13–17 and employed a two-stage sample design involving a school and class level. We sampled 64 schools, including 320 classes from grades 7–11. The ten core questionnaire modules address the leading causes of morbidity and mortality among children and adults worldwide. The overall response rate was 89%, 3,685 (51.1%) were males. 5,843 (84.5%) were between the ages of 13 to 17. Almost 40% were overweight, and 18.2% of the students were obese. Overall, 1,452 (23%) of the students were not physically active, with a higher representation of the female students; 774 (53%). About 27% have smoked cigarettes, 70.7% of whom are males, and 3.1% of students reported using drugs, 76% of them are males. 616 (19%) of students had food from fast-food restaurants for five or more days of the week. 24% never or rarely consumed breakfast, while 47% consumed fruits less than once per day, of whom 53% are female. The survey showed alarming rates of obesity, overweight and unhealthy food practices among school students. The lifestyle behaviours identified in this study will inform community-based intervention to help the country develop priorities, establish programs and advocate for resources for school health programs.